Du vandalisme d’art comme stratégie de captation de l’attention - Anne Bessette (Recherches Sociologiques et Anthropologiques, 2023)
This article aims to contribute to the analysis and understanding of acts of vandalism perpetrated on works exhibited in art museums. In the context of a museum, it seems unlikely that detection and the consequences of tampering with a work of art can be avoided: what is it that prompts people to take this risk? What drives these actions? The reactions their actions give rise to indicate that the perpetrators are hitting a nerve by attacking works of art in museums, artefacts invested with a special social status. It is particularly significant that acts of vandalism perpetrated against works exhibited in art museums are often perceived as senseless and irrational. The article will go on to question these representations on the one hand and, on the other, the disparities in social reactions generated by acts of art vandalism.